Three-dimensional (3D) reconstruction of computer tomography cardiac images using visualization toolkit (VTK) / Mohammad Zahid Zamaludin - Mohammad Zahid , Zamaludin (2021)
Cardiac study proves to be important to diagnose and treat cardiovascular disease that accounts for 20% of death in the world. Three-dimensional (3D) images of the heart are important to understand its real structure, functions and physical abnormalities occurring in the tissue. The objective of this paper is to reconstruct 3D images from 2D CT Scan slices of the cardiac region of interest using Visualisation Toolkit (VTK). The Visualization Toolkit (VTK) is non-propriety software with state-of-the-art tools for 3D rendering that is easily customizable programming. 3D images are reconstructed using surface rendering technique and volume rendering technique. Volume rendering shows best rendering quality compared to surface rendering when reconstructing cardiac 3D images. Artery structure are easily identifiable using volume rendering in VTK whereas surface rendering image yielded false positive or false negative images. VTK capabilities are also compared RadiAnt DICOM Viewer. The 3D image rendered match the quality of RadiAnt 3D image.